THE ROLE OF COMPANY SIZE IN MODERATING THE EFFECT OF AUDIT TENURE, PROFITABILITY, COMPANY RISK AND COMPANY COMPLEXITY ON AUDIT FEES WITH AUDIT QUALITY AS A MEDIATOR - Mohamad Zulman Hakim; Siti Nurhayati; Novita Dwi Safitri; Dini Ramadhanty; Nur Mala (ZILLZELL MEDIA PRIMA, 2026)
Influence of audit tenure, profitability, company risk, and company complexity on audit fees with company quality as a mediator. The research subjects included banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The analysis method used was panel data regression with the help of Eviews software version 12. Based on the test results, several findings were obtained, namely: (1) Audit tenure does not affect audit fees; (2) Profitability has a significant effect on audit fees; (3) Company risk does not affect audit fees; (4) Company complexity also does not affect audit fees. Furthermore, the results of the moderation test show that: (5) Company size is unable to moderate the relationship between audit tenure and audit fees; (6) Company size is able to moderate the relationship between profitability and audit fees; (7) Company size is unable to moderate the relationship between company risk and audit fees; (8) Company size is unable to moderate the relationship between company complexity and audit fees. In addition, the results of the mediation test show that: (9) Audit Quality cannot mediate the relationship between Audit Tenure and Audit Fee; (10) Audit Quality can mediate the effect of Profitability on Audit Fee; (11) Audit Quality cannot mediate the effect of Company Risk on Audit Fee; and (12) Audit Quality cannot mediate the effect of Company Complexity on Audit Fee.